Evaluation of Ergonomic Conditions in Administrative Offices to Enhance Occupational Health - Gavilánez Quintana, Erika Paola (Artes: Architecture, Technology and Sustainability, 2024)
Musculoskeletal disorders in administrative settings significantly affect worker productivity and well-being, largely due to a lack of adequate ergonomic conditions in the workplace. Ergonomics seeks to improve staff health and comfort by reducing physical and mental strain. This study analyzed the impact of ergonomic design on workstations, evaluating aspects such as furniture layout, employee posture, and equipment adequacy. Through observation and two surveys conducted with eight employees in a design office, various factors contributing to fatigue and musculoskeletal discomfort were identified. Following the implementation of simple ergonomic improvements, a significant reduction in muscle fatigue and an increase in productivity were evident. These findings highlight the importance of ergonomic design in offices, demonstrating its positive impact on occupational health and job performance.